Question :

enter image description here

My approach :

Now as I had to obtain a remainder of $\frac{(x-1)^{2017}}{x^2 - x +1}$ So, I could write this as $\frac{(x-1)^{2017}}{(x - 1)^2 + x}$

now I substitute $t = (x-1)$, so $\frac{(x-1)^{2017}}{(x - 1)^2 + x}$ could be written as $\frac{t^{2017}}{t^{2} + t + 1}$

From here we can easily obtain the remainder by plain division itself, so $P^{1}(x) = -(t+1)t^{2015} = -x(x-1)^{2015}$

Since we need $P^{2017}(2016)$, using the above obtained $P^{1}(x)$, I first obtained $P^{1}(2016) = -2016(2015)^{2015}$.

Similarly $P^{2}(x) = -P^{1}(x)(P^{1}(x) - 1)^{2015}$ by question definition, but there's no further way to simplify it, and also $P^{n}(x)$ gets bigger and bigger as $n$ increases.

So I genuinely feel this approach is wrong way, so could you help me out upon this question ?

  • $\begingroup$ But.. Doesn't it satisfy $a = bq + r$ ?? $\endgroup$ – Arnav Das Nov 30 '16 at 16:49


You mean remainder right, not quotient.


As $3|2016, t^{2016}\equiv1$

$\implies t^{2017}\equiv t$


$p(x) = q(x) d(x) + P^1(x)$

$P^{1}(x)$ is at most a 1 degree polynomial

If $\omega$ is a root of $d(x).$ $p(\omega) = P^1(\omega)$

From this we find $P^{1}(\omega_1), P^{1}(\omega_2)$ and the line between them.

$\omega_1, \omega_2 = \frac 12 + i \frac {\sqrt 3}{2}, \frac 12 - i \frac {\sqrt 3}{2}$

$p(\omega_1) = $$(-\frac 12 + i \frac {\sqrt 3}{2})^{2017}\\ e^{\frac {2017\cdot2 \pi}{3}}\\ -\frac 12 + i \frac {\sqrt 3}{2}\\ \omega_1 - 1$

$p(\omega_2) = \omega_2 - 1$

$P^1(x) = x-1$

$P^2(x) =$$ P^1(P^1(x))\\ x-2$

$P^{k}(x) =x-k$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.